THE INFLUENCE OF INFORMATION TECHNOLOGY AND COMPUTER-BASED AUDIT SYSTEMS ON AUDIT QUALITY - Olga Sarah Theresia Sagala; Rolyana Ferinia Pintauli; HIsar Pangaribuan (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study aims to analyze the strengths of Information Technology, Computer-Based Audit Systems, and Audit Quality at Mirawati Sensi Idris Public Accounting Firm and to examine the effect of Information Technology on Audit Quality, the effect of Computer-Based Audit Systems on Audit Quality, the effect of Information Technology on Computer-Based Audit Systems, and the indirect effect of Information Technology on Audit Quality through Computer-Based Audit Systems as a mediating variable. This study uses a quantitative approach with a correlational design. Data were collected through a 1–5 Likert scale questionnaire administered to 72 auditors selected using convenience sampling based on the availability and willingness of respondents. Data analysis was performed descriptively and inferentially using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through SmartPLS 4.0. The results showed that all variables were in the good category. Hypothesis testing proved that Information Technology and Computer-Based Audit Systems had a positive and significant effect on Audit Quality, Information Technology had a positive and significant effect on Computer-Based Audit Systems, and Computer-Based Audit Systems positively and significantly mediated the relationship between Information Technology and Audit Quality. These findings indicate that the integration and optimization of technology in digital audit systems play an important role in improving audit quality.